2009
DOI: 10.1111/j.1742-481x.2009.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Dilemmas in measuring and using pressure ulcer prevalence and incidence: an international consensus

Abstract: Pressure ulcer prevalence and incidence data are increasingly being used as indicators of quality of care and the efficacy of pressure ulcer prevention protocols. In some health care systems, the occurrence of pressure ulcers is also being linked to reimbursement. The wider use of these epidemiological analyses necessitates that all those involved in pressure ulcer care and prevention have a clear understanding of the definitions and implications of prevalence and incidence rates. In addition, an appreciation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
1
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(73 citation statements)
references
References 26 publications
1
65
1
5
Order By: Relevance
“…The cumulative incidence of pressure injuries was calculated by dividing the total number of new cases of pressure injuries, multiplied by 100, by the total number of participants in the time period. [31][32][33] Kaplan-Meier survival analysis was used to compare time to new pressure injury events between the 2 groups. A 2 test of independence was used to determine differences in stages of pressure injuries and to determine differences in process of care practices delivered between the groups.…”
Section: B Strategies To Prevent Pressure Injuriesmentioning
confidence: 99%
“…The cumulative incidence of pressure injuries was calculated by dividing the total number of new cases of pressure injuries, multiplied by 100, by the total number of participants in the time period. [31][32][33] Kaplan-Meier survival analysis was used to compare time to new pressure injury events between the 2 groups. A 2 test of independence was used to determine differences in stages of pressure injuries and to determine differences in process of care practices delivered between the groups.…”
Section: B Strategies To Prevent Pressure Injuriesmentioning
confidence: 99%
“…However, it is recognized that prevalence data is a snapshot and not a true reflection of the scope of a given problem [12] . Incidence data provides a more accurate picture of the magnitude of a problem.…”
Section: Introductionmentioning
confidence: 99%
“…Incidence data provides a more accurate picture of the magnitude of a problem. However, incidence data presents problems with lengthy and time consuming data collection [12] . Critically ill patients in ICU are considered to be at greatest risk for PrU development, as this patient group is likely to present with high acuity, may require mechanical ventilation and subsequent administration of sedation and pharmacological drugs potentially reducing peripheral circulation and be immobile [13,14] .…”
Section: Introductionmentioning
confidence: 99%
“…It is probable that the acute in-patient pressure ulcer numbers were considerably underestimated. Several studies in other countries have suggested that hospital patient records do not always capture adequate information about pressure ulcers (Baharestani et al 2009;Gunningberg and Ehrenberg 2004) and that inadequate documentation, particularly of lower-stage ulcers, is common in both nurses' and doctors' notes. Furthermore, while there is good coverage in the acute in-patient setting across most of Canada, the home care and complex continuing care data focus primarily on Ontario.…”
Section: Discussionmentioning
confidence: 99%